Fordyce Angiokeratoma: Comparison of Cryotherapy and Electrocauterization Treatments - Necmi Bayraktar (Dermatology Research and Practice)
Fordyce angiokeratoma is a benign lesion commonly developing on the scrotal skin. The incidence increases with age. About half of these lesions may be symptomatic and frequently cause itching and bleeding. Although the treatment is not always considered necessary, several treatment methods are used for symptomatic cases, especially for cosmetic purposes. Treatment options include surgical excision, laser ablation, electrocoagulation, cryotherapy, and sclerotherapy. The most widely used methods are electrocoagulation and cryotherapy. Although these two methods are similarly effective and safe, there are differences in means of patient comfort and cosmetic outcomes. Patient comfort can be defined as pain management during the procedure and the healing period. Bleeding and wound infection are other parameters that may decrease patient comfort. Patients would prefer treatment methods with less or no pain and shorter recovery periods, healthcare providers, and insurance. The cosmetic result is another critical issue, especially for patients with multiple lesions. Treatment methods avoiding genital scars are more likely to meet the aesthetic demands of the patients.